2011
DOI: 10.1007/s12032-011-9903-2
|View full text |Cite
|
Sign up to set email alerts
|

The correlation between tumor-infiltrating Foxp3+ regulatory T cells and cyclooxygenase-2 expression and their association with recurrence in resected head and neck cancers

Abstract: The aim of this study was to investigate the correlation between tumor-infiltrating CD4+ CD25(high) Foxp3+ naturally occurring regulatory T cells (Foxp3+ nTregs) and cyclooxygenase-2 (COX-2) expression and their association with local recurrence in resected head and neck cancers. Intratumoral COX-2 and Foxp3+ nTregs expressions were retrospectively assessed using immunohistochemistry. Associations between the clinicopathological characteristics and either intratumoral COX-2 expression or number of Foxp3+ nTreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 23 publications
1
24
0
Order By: Relevance
“…In the oral cavity, FoxP3+ TIL have been shown to be unfavorable when in high numbers intratumorally and peritumorally, which suggests that oral cavity tumors prosper in environments where the inflammatory response is dampened. The opposite correlation with clinical outcome, however, was seen in oropharyngeal tumors and both positive and negative associations were shown in studies of combined head and neck cancer subsites.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In the oral cavity, FoxP3+ TIL have been shown to be unfavorable when in high numbers intratumorally and peritumorally, which suggests that oral cavity tumors prosper in environments where the inflammatory response is dampened. The opposite correlation with clinical outcome, however, was seen in oropharyngeal tumors and both positive and negative associations were shown in studies of combined head and neck cancer subsites.…”
Section: Discussionmentioning
confidence: 94%
“…Other T‐lymphocyte populations, CD3+, CD4+, and CD25+, have also demonstrated favorable features when observed in higher numbers . Interestingly, the effect of FoxP3+CD4+T‐reg cells has been shown to be beneficial and detrimental in an equal number of studies. FoxP3+ cells may behave differently in different anatomic subsites, which might explain this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…9 studies were excluded as they did not provide sufficient data for extracting odds ratio (OR) or hazard ratio (HR) or 95% confidence intervals (CI) [2836], leaving 29 studies that fulfilled the eligibility criteria [2227, 3759] (Table 1). Four studies reported no site-specific HNC [24, 5457] and others recorded site-specific HNC. There were 7, 6 and 9 studies focused on oral cancer (OC) [22, 25, 27, 3740], laryngeal cancer (LC) [4146] and nasopharyngeal cancer (NPC) [23, 26, 4753], respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Immunohistochemical studies revealed that COX-2 overexpression was positively correlated with the number of tumor-infiltrating Foxp3+ regulatory T cells in the local microenvironment of HNSCC. This suggests that COX-2 facilitated the expansion of the regulatory T cells through PGE 2 150.…”
Section: Hnscc-associated Inflammationmentioning
confidence: 91%